Knowledge-oriented database formation for determination of complex method for quality identification of compound systems - Козуля, Тетяна Володимирівна; Шаронова, Наталья Валеріївна; Козуля, Марія Михайлівна; Святкін, Ярослав Володимирович (Eastern-European Journal of Enterprise Technologies, 2016)
Feasibility substantiation of resorting to the provisions of synergy and the theory of nonlinear processes of compound systems in modeling the system object behavior is considered. Any self-organizing system of social, ecological and economic content is open dissipative, which removes entropy growing in destructive phenomena in the interaction with the environment. The use of the entropic approach to the analysis of complex objects allowed reviewing the structure of the analytical system and representing it as "0-state of the object - process - i-state of the object", the estimate of which is agreed due to the versatility of quantitative analysis based on the entropy function. The proposed analytical system allows applying methodical approaches to solving complex problems for safety evaluation of different objects of the study. Software for implementing the complex method for quality evaluation of compound systems is provided. The proposed software allows speeding up the solution of problems regarding the computation of the overall state of the object with the identification of risk factors using the considered method. The computer application with the user-friendly interface is made, which allows displaying results in an analytical form and in the form of graphs. This simplifies the perception of information regarding the research results obtained.